Multimodal Discourse Analysis of Indomie Advertisements on Television - Ifa Iswatul Hasan; Ana Fikrotuz Zakiyah; Unsil Faida (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study investigates how Indomie television advertisements employ multimodal elements to convey persuasive messages and construct cultural identity. It aims to examine the integration of visual, linguistic, spatial, and auditory modes in shaping consumer perception and fostering brand loyalty. Using a qualitative descriptive-interpretative method, five advertisements aired between 2020 and 2024 were purposively selected and analyzed within a multimodal discourse analysis framework. The findings reveal that these advertisements combine everyday domestic settings, emotive language, relatable characters, and culturally rooted music to depict themes of togetherness, comfort, and national pride. Visual features such as animated steam, bright colors, and direct gaze enhance emotional engagement, while memorable slogans like “Indomie seleraku” personalize the brand experience. The study concludes that Indomie’s advertising transcends product promotion by embedding narratives of cultural familiarity and shared values, positioning the product as a symbol of national identity. These results underscore the persuasive power of multimodal strategies in food advertising and suggest avenues for future research in cross-cultural advertising discourse. Keywords: Multimodal, Discourse, advertising